Chloramphenicol-associated aplastic anemia: A review - Sanatkumar Bharamu Nyamagoud; Agadi Hiremath Viswanatha Swamy; Nisthul Stanly; Christen Tom; Vishwanath Hegadal; D. B. Bhavya (BLDE University Journal of Health Sciences)
The utilization of the broad-spectrum antibiotic chloramphenicol has been associated with the occurrence of a negative outcome recognized as aplastic anemia. This outcome is infrequent yet carries significant gravity. This study provides a comprehensive analysis of chloramphenicol-associated aplastic anemia, including its epidemiology, clinical features, diagnostic approaches, proposed mechanisms, treatment outcomes, risk factors, and reporting characteristics. Epidemiological data indicate the variations in the incidence rates across different populations, with higher rates observed in Southeast Asia. The clinical features include pancytopenia, fatigue, pallor, infections, and bleeding tendencies, with variations in disease severity and progression. Diagnostic approaches involve evaluating clinical history, physical examination findings, and laboratory investigations, although challenges and limitations exist in diagnosing this condition. Management strategies encompass supportive care, blood transfusions, and hematopoietic stem cell transplantation for severe cases. Risk factors encompass genetic predisposition, patient age, duration of exposure, and concurrent medication utilization. Reporting bias and publication characteristics are evaluated, highlighting the need for future research. This study provides valuable insights into chloramphenicol-associated aplastic anemia, aiding clinicians in recognizing and managing this adverse effect.